Generation of tourist movement on the example of innovative state and private partnership in health resort city of Soletz-Zdruy - Paweł Patrzałek; Artur Łachut (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
In spite of high competitiveness and turbulence of tourist environment Poland is an attractive region for travelling. The available variety of forms for active rest (geodesic conditions), rich cultural heritage, favorable natural conditions and health resort values determine the attraction of Polish tourist potential on the European map. The example of the health resort city of Soletz-Zdruy confirms the empiric data concerning the dynamic stimulation of tourist movement during a short period. The state and private partnership and right choice of the business components determine success at the market and make competitive advantages. The current research shows that the population is getting older and the educated Polish society is looking for the natural ways of spiritual and physical health protection. The main environment for accurate search of a suitable place for trips is Internet. Knowledge, professionalism and the quality of providing services influence upon the choice of a tourist product.